Temperature Gradient and Its Effect on Long-Span Prestressed Concrete Box Girder Bridge - B. Gu; F. Y. Zhou; W. Gao; F. Z. Xie; L. H. Lei (Advances in Civil Engineering)
Temperature variations in the girder at two cross-sections of a long-span prestressed concrete box girder bridge (PCBG) were analysed based on measured data. The results show that the temperature distribution in the concrete box girder (CBG) is strongly influenced by its size, and the temperature distribution in the girder changes along the longitudinal direction of the bridge. To clarify the temperature distribution in the long-span PCBG bridge, a two-dimensional (2D) temperature prediction model, validated by the measured data, was proposed, and the effect of the girder size on the temperature distribution of the CBG was studied using the model. Based on the results of the studies, simplified vertical and transverse temperature gradient models that could consider changes along the longitudinal direction of the bridge were proposed and validated by using the measured data and three-dimensional (3D) mechanical finite element model (FEM) of the bridge. Then, the deformations and stresses derived from the proposed temperature gradient models and the models according to different codes were studied and compared. Finally, conclusions and recommendations for future bridge design are provided.